Effect of the Mode of Application of Cryopreserved Human Amniotic Membrane on Adhesion Formation after Abdomino-Pelvic Surgery in a Mouse Model - Nassif, Joseph; Abbasi, Sehrish A.; Kechli, Mohamad Karim; Boutary, Suzan S.; Ghulmiyyah, Labib; Khalifeh, Ibrahim; Abou Ghaddara, Hussein; Nassar, Anwar H. (Frontiers in Medicine, 2016)
Adhesions after abdomino-pelvic surgery are a cause of morbidity and reoperations. The use of human amniotic membrane (HAM) for adhesion prevention has given controversial results. The mode of administration of the amniotic membrane has not been well studied. This study assessed the efficacy of two modes of application of cryopreserved HAM, patch or fragmented in Lactated Ringer solution, for the prevention of pelvic adhesion formation post abdomino-pelvic surgery in a mice model. After a midline laparotomy incision, a small cautery lesion was done on each side of the abdominal wall peritoneum in mice. In Group A (control; n=42) the abdomen was closed directly, Group B (n=42) received 2.5 ml of Lactated Ringer (LR) prior to closure. In Groups C (n=42) and D (n=42), a 2x2 cm patch of HAM and another one fragmented and dispersed in 2.5 ml of LR were applied prior to closure, respectively. Two weeks later, a laparotomy was performed and gross and pathological evaluation of adhesions, fibrosis, angiogenesis, and inflammation were conducted. Group D exhibited a significantly lower rate of gross adhesion formation. Fibrosis was significantly lowest in Group C as compared to the control. Group B had the lowest vascular formation in the adhesions. The use of HAM fragmented in LR solution is associated with a significantly lower incidence of postoperative adhesions in mice when compared to LR alone, HAM patch or control. The mechanism of action of this reduction needs to be elucidated by future studies.